Analysis and determination of solar potential using models based on climatic parameters for the district of San Mateo, province of Huarochiri, Lima Peru - Andía M. (2021)
It shows the analysis and determination of solar potential throght models based on climatic parameters for the district of San Mateo, Province of Huarochiri, located in Lima, Peru